Safeguards Assessments Policy : External Expert Panel's Advisory Report. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2015)
This report by the external expert panel ('the panel') examines the effectiveness and appropriateness of the safeguards assessments policy in the five years since its last review in 2010. In addition to expressing an opinion on the effectiveness and appropriateness of the safeguards assessment policy, the panel also makes recommendations to the Executive Board for its consideration to improve and optimize the benefits to be garnered from the safeguards assessment policy. The panel's opinion is based on (i) consultations with key stakeholders, including central bank authorities, IMF Executive Directors' offices, Fund and World Bank staff; (ii) examination of safeguards assessment and other Fund-specific documents; and (iii) study of international reference materials.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet